Induction and Enhancement of Antimicrobial Activity Produced by Fungal Isolates - Nor R, Mat; Ariffin Z, Zainal; Noor Z, Mohd; Rahman Z, Abd (Malaysian Journal of Science, 2005)
Eight fungal isolates, which were isolated from soil samples, were used in the study. The isolates were identified as Aspergillus sp. (three isolates), Trichoderma sp. (two isolates) and Penicillium sp. (three isolates). All isolates were introduced to live cells of pathogenic bacteria, Pseudomonas aeruginosa. All antibiotic producing isolates showed enhanced antimicrobial activity towards Bacillus subtilis, and one of the non antibiotic producing isolates was induced to produce similar compound. The results suggested that the production of antimicrobial compounds produced by soil fungi can be induced or enhanced by the presence of pathogenic bacteria.